A Population-Based Assessment of the Impact of 7- and 13-Valent Pneumococcal Conjugate Vaccines on Macrolide-Resistant Invasive Pneumococcal Disease: Emergence and Decline of Streptococcus pneumoniae Serotype 19A (CC320) With Dual Macrolide Resistance Mechanisms. (10th July 2017) - Schroeder, Max R; Chancey, Scott T; Thomas, Stephanie; Kuo, Wan-Hsuan; Satola, Sarah W; Farley, Monica M; Stephens, David S
Summary: Macrolide-resistant Streptococcus pneumoniae containing both mef (E)/ mel and erm (B) rapidly expanded (2005–2009) but decreased following pneumococcal conjugate vaccine 13 introduction. Macrolide-resistant serotypes not represented in vaccines increased modestly. Selective pressures of macrolide use and vaccine introductions were associated with these changes. Abstract: Background: Macrolide efflux encoded by mef (E)/ mel and ribosomal methylation encoded by erm (B) confer most macrolide resistance in Streptococcus pneumoniae . Introduction of the heptavalent pneumococcal conjugate vaccine (PCV7) in 2000 reduced macrolide-resistant invasive pneumococcal disease (MR-IPD) due to PCV7 serotypes (6B, 9V, 14, 19F, and 23F). Methods: In this study, the impact of PCV7 and PCV13 on MR-IPD was prospectively assessed. A 20-year study of IPD performed in metropolitan Atlanta, Georgia, using active, population-based surveillance formed the basis for this study. Genetic determinants of macrolide resistance were evaluated using established techniques. Results: During the decade of PCV7 use (2000–2009), MR-IPD decreased rapidly until 2002 and subsequently stabilized until the introduction of PCV13 in 2010 when MR-IPD incidence decreased further from 3.71 to 2.45/100000 population. In 2003, serotype 19A CC320 isolates containing both mef (E)/ mel and erm (B) were observed and rapidly expanded in 2005–2009, peaking in 2010 (incidence 1.38/100000 population), accounting for 36.1% of MR-IPD and 11.7% of all IPD isolates. Following PCV13 introduction, dual macrolide-resistant IPD decreased 74.1% (incidence 0.32/100000 in 2013). However, other macrolide-resistant serotypes (eg, 15A and 35B) not currently represented in PCV formulations increased modestly. Conclusions: The selective pressures of widespread macrolide use and PCV7 and PCV13 introductions on S. pneumoniae were associated with changes in macrolide resistance and the molecular basis over time in our population. Durable surveillance and programs that emphasize the judicious use of antibiotics need to continue to be a focus of public health strategies directed at S. pneumoniae .